(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
Nowadays, the field of education is developing in all countries around the world. Higher education remains a key component of this educational system. In order for higher education leaders to successfully manage their institutions, they must continuously acquire a wide range of skills that are in line with the demands of today’s innovative era. Through constant self-development, leaders can bring significant benefits to the advancement of their institutions. One of the essential skills that any leader must possess is strategic thinking. Leaders with this skill are able to make decisions with a long-term perspective, which is one of the critical factors in the development of educational institutions.